Estratégias de seleção no melhoramento genético de Eucalyptus camaldulensis em Mato Grosso - Souza, Thaianny Rodrigues de (2015)
For the success of enhancements programs it`s necessary a good genetic material available, favorable environmental factors and selection methods appropriate to the program objectives. In this context, this study aimed to evaluate the current genetic variability as well as suitable screening methods for a population of Eucalyptus camaldulensis in progeny test. Eucalyptus camaldulensis Dehnh is a species that stands out in the Eucalyptus genus, with extensive plasticity, adaptability and multiple use. The experiment is installed at the Santo Antônio de Leveger county in the Brazilian state of Mato Grosso - containing 117 progenies, in a randomized blocks conducted experiment. The results obtained through genetic parameters indicated individual heritability and average magnitude of average progenies for DAP characters and FF and low magnitude to ALTT, ALTC and SOB. indicating some genetic control. It was detected genetic variability for the traits analyzed in the population of Eucalyptus camaldulensis with possibilities of genetic gains following the enhancement program. The selection among and within families and the combined screening, indicate the possibility of genetic gains, however individual screening allowed maximize gains for the studied characters.